Blue straggler stars in Galactic open clusters and the effect of field star contamination - Carraro, G. (2008)
Context. We investigate the distribution of blue straggler stars in the field of three open star clusters. Aims. The main purpose is to highlight the crucial role played by general Galactic disk fore-/back-ground field stars, which are often located in the same region of the color magnitude diagram as blue straggler stars. Methods. We analyze photometry taken from the literature of 3 open clusters of intermediate/old age rich in blue straggler stars, which are projected in the direction of the Perseus arm, and study their spatial distribution and the color magnitude diagram. Results. As expected, we find that a large portion of the blue straggler population in these clusters are simply young field stars belonging to the spiral arm. This result has important consequences on the theories of the formation and statistics of blue straggler stars in different population environments: open clusters, globular clusters, or dwarf galaxies. Conclusions. As previously emphasized by many authors, a detailed membership analysis is mandatory before comparing the blue straggler population in star clusters to theoretical models. Moreover, these sequences of young field stars (blue plumes) are potentially powerful tracers of Galactic structure and they require further consideration.